Experience and Entrepreneurship: A Career Transition Perspective. (October 2019) - Rider, Christopher I.; Thompson, Peter; Kacperczyk, Aleksandra; Tåg, Joacim
The authors cast entrepreneurship as one of three career choices—remaining with one's employer, changing employers, or engaging in entrepreneurship—and theorize how the likelihood of entrepreneurship evolves over one's career. They empirically demonstrate an inverted U-shaped relationship between accumulated experience and entrepreneurship across various industries and jobs. The authors highlight the difficulty of inferring the mechanism underlying the observed relationship, despite detailed career history data and job displacement shocks that eliminate the current employer choice. These analyses motivate a formal career transitions model in which employer-specific and general skills accumulate with experience but potential employers observe only total skill. Results from the model presented here are that entrepreneurial career transitions vary with two relative costs: 1) the cost to an individual to form a business and 2) the cost to a potential employer to utilize the individual's employer-specific skills. The authors discuss how this model contributes new insights into an entrepreneurial career.